2020
DOI: 10.1002/lio2.492
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of peak expiratory flow percentage compared to endoscopic grading in subglottic stenosis

Abstract: Objective: To determine the reliability of pulmonary function testing compared to endoscopic grading in the assessment of subglottic stenosis. Methods: Consecutively treated patients with subglottic stenosis at a tertiary care specialty hospital from 2009 to 2019 were identified. Two fellowship-trained laryngologists and two otolaryngologists blinded to clinical history reviewed laryngo tracheoscopic examinations and assessed the degree of stenosis using the Cotton-Myer grading system (% stenosis). Nine full f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…One study found endoscopic grading of stenosis may have poor reliability compared to PFTs, and another found no correlation between grading of stenosis and PFTs [66,67]. However, peak expiratory flow has been shown to be a simple measurement to monitor iSGS progression with a sensitivity and specificity of 84.4% and 82.0%, respectively [68].…”
Section: Diagnosis and Preoperative Evaluationmentioning
confidence: 99%
“…One study found endoscopic grading of stenosis may have poor reliability compared to PFTs, and another found no correlation between grading of stenosis and PFTs [66,67]. However, peak expiratory flow has been shown to be a simple measurement to monitor iSGS progression with a sensitivity and specificity of 84.4% and 82.0%, respectively [68].…”
Section: Diagnosis and Preoperative Evaluationmentioning
confidence: 99%
“…14 Lately, PEF%-as the patient's measured PEF divided by the predicted PEF for someone of the same age, height, and sexwas proposed as a standardized spirometry measurement to describe disease severity in patients with subglottic stenosis. 18,20 Furthermore, Naunheim et al sought to identify associations between PEF% and specific questions from a range of quality of life instruments. 20 According to the American Thoracic Society, breathlessness should be measured regardless of its cause, to be assessed properly.…”
mentioning
confidence: 99%
“…At least 6 months after surgical treatment objective ventilatory function was evaluated on the basis of the flow-volume loop obtained by a spirometer. Pulmonary function test (PFT) was performed on all patients measuring the postoperative peak expiratory flow (PEF), a well-established objective parameter to evaluate the extent of residual airway obstruction [21][22][23]. The decannulation rate was a secondary outcome, measurable for the cohort of patients with a tracheostomy at the time of the surgical procedure (n = 12, 30%).…”
Section: Airway Evaluationmentioning
confidence: 99%